Financial institutions management : a risk management approach - Saunders, Anthony, 1949-; Cornett, Marcia Millon (New York, NY : McGraw-Hill, 2011)
Provides an approach that focuses on managing return and risk in modern financial institutions. This title analyzes the traditional nature of each sector's product activity, emphasising on the various areas of activities such as asset securitization, off-balance-sheet banking, and international banking.
Includes index.
oif 05/09/14
Loan
Keywords: Financial institutions -- United States -- Management; Risk management -- United States; Financial services industry -- United States -- Management